2018
DOI: 10.1139/apnm-2017-0408
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rolling massage on the excitability of the corticospinal pathway

Abstract: The aim of the present study was to investigate the alterations of corticospinal excitability (motor evoked potential, MEP) and inhibition (silent period, SP) following rolling massage of the quadriceps muscles. Transcranial magnetic and femoral nerve electrical stimuli were used to elicit MEPs and compound muscle action potential (Mmax) in the vastus lateralis and vastus medialis muscles prior to and following either (i) 4 sets of 90-s rolling massage (ROLLING) or (ii) rest (CONTROL). One series of neuromuscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 31 publications
2
45
0
Order By: Relevance
“… 104 105 Similarly, foam rolling (tool-assisted massage of myofascial tissues) seems to improve short-term flexibility and recovery from muscle soreness 75 106 107 and decrease latent trigger point sensitivity. 103 Nevertheless, the physiological mechanisms of these reported effects remain unclear, although initial evidence suggests increases in arterial perfusion, enhanced fascial layer sliding and modified corticospinal excitability following treatment 108 109 (F Krause et al , submitted, 2018). Finally, manual therapies, such as massage, osteopathy or Rolfing (a massage technique based on achieving symmetrical alignment of the body), are frequently used to improve fascial tissue regeneration or athletic performance, although their efficacy still remains to be validated.…”
Section: Consensus Meetingmentioning
confidence: 99%
“… 104 105 Similarly, foam rolling (tool-assisted massage of myofascial tissues) seems to improve short-term flexibility and recovery from muscle soreness 75 106 107 and decrease latent trigger point sensitivity. 103 Nevertheless, the physiological mechanisms of these reported effects remain unclear, although initial evidence suggests increases in arterial perfusion, enhanced fascial layer sliding and modified corticospinal excitability following treatment 108 109 (F Krause et al , submitted, 2018). Finally, manual therapies, such as massage, osteopathy or Rolfing (a massage technique based on achieving symmetrical alignment of the body), are frequently used to improve fascial tissue regeneration or athletic performance, although their efficacy still remains to be validated.…”
Section: Consensus Meetingmentioning
confidence: 99%
“…For example, high-intensity foam rolling or rolling massage may decrease the contralateral or nonlocal muscle mechanical sensitivity (Aboodarda, Spence & Button, 2015; Cavanaugh et al, 2017b; Cheatham & Baker, 2017; Cheatham, Stull & Kolber, 2019), thereby leading to an enhancement of the stretch tolerance of these muscles. Recent work from Behm’s group (Aboodarda et al, 2018; Cavanaugh et al, 2017a; Young, Spence & Behm, 2018) showed that the intervention of foam rolling or rolling massage could even cause the reduction of excitability at the muscular, spinal, and supraspinal levels. Thus, with the decreased corticospinal (Aboodarda et al, 2018) and spinal (Young, Spence & Behm, 2018) excitabilities, it is interesting and important to examine if there are any central-mediated changes on the contralateral or nonlocal muscles, due to the intervention of unilateral SAFR.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the force applied, there arises the question whether greater pressure exerted on tissues provides greater therapeutic effects. Aboodarda et al [1] described high muscle vertical pressure as a 1-3 cm deep muscle therapy, but they obtained this outcome with a hard rubber roller massager and the command not to produce a greater value than 7/10 on the Visual Analogue Scale. There is a tendency to use a command such as AMAP -as much pressure as possible -and AMAT -as much pressure as tolerable.…”
Section: Introductionmentioning
confidence: 99%